2017
DOI: 10.6061/clinics/2017(11)07
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of the short-term outcomes of patients with hepatitis B virus-associated acute-on-chronic liver failure

Abstract: OBJECTIVE:To investigate the impact of the baseline status of patients with hepatitis B virus-associated acute-on-chronic liver failure on short-term outcomes.METHODS:A retrospective study was conducted that included a total of 138 patients with hepatitis B virus-associated acute-on-chronic liver failure admitted to the Department of Infectious Diseases, Taihe Hospital, Hubei University of Medicine, from November 2013 to October 2016. The patients were divided into a poor prognosis group (74 patients) and a go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…It is consistent with the level of protein metabolism and has been extensively reported in kidney disease, diabetes, pregnancyinduced hypertension, and fever following Transcatheter Arterial Embolization (TAE) (10)(11)(12)(13). In a previous prospective study, Lei et al suggested that serum urea could predict short-term outcomes of patients with hepatitis B virusassociated Acute-on-chronic Liver Failure (ACLF) (14). Mjasnikova et al suggested that serum urea was associated with the Model for End-stage Liver Disease (MELD) score in HCV-induced liver cirrhosis, as well as with esophageal vein bleeding (15).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is consistent with the level of protein metabolism and has been extensively reported in kidney disease, diabetes, pregnancyinduced hypertension, and fever following Transcatheter Arterial Embolization (TAE) (10)(11)(12)(13). In a previous prospective study, Lei et al suggested that serum urea could predict short-term outcomes of patients with hepatitis B virusassociated Acute-on-chronic Liver Failure (ACLF) (14). Mjasnikova et al suggested that serum urea was associated with the Model for End-stage Liver Disease (MELD) score in HCV-induced liver cirrhosis, as well as with esophageal vein bleeding (15).…”
Section: Introductionsupporting
confidence: 76%
“…The results of Lei et al's study indicated that serum urea was significantly associated with the short-term outcomes of hepatitis B virus-associated acute-on-chronic liver failure (14). Hence, we assume that the level of urea is a comprehensive marker of gastrointestinal hemorrhage, protein metabolism, and kidney function, which strongly impacts the prognosis of DeCi patients.…”
Section: Discussionmentioning
confidence: 92%
“…Various score models have been proposed to predict the prognosis of liver failure[14,33]. In this study, MELD, MELD-Na, iMELD, CTP, and ALBI scores were all markedly higher in HBV-ACLF patients with infections than in their counterparts without infections.…”
Section: Discussionmentioning
confidence: 61%
“…Model for End-Stage Liver Disease (MELD) score, MELD-sodium (MELD-Na) score, integrated MELD (iMELD) score, Child-Turcotte-Pugh (CTP) score, albumin-bilirubin (ALBI) score, and the ACLF grading system were used as described in the previous literature[2,14]. CTP score is the cumulative result of the scores for five items (ascites, hepatic encephalopathy, TBIL, Alb, and PT extension time), with 1-3 points for each item and a maximum of 15 points.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Gao et al combined neutrophil to lymphocyte ratio (NLR), HE, INR, age and TBIL to construct a prediction model for 90-day mortality of HBV-ACLF, which showed better predictive values in comparison with MELD, MELD-Na, and CTP [25]. Lei et al proposed a formula model based on NLR, GGT, albumin, sodium and artificial liver support therapy to predict short-term mortality of HBV-ACLF [26]. Chen et al combined age, serum sodium and MELD score to develop a prognostic nomogram to assess 3-month mortality of HBV-ACLF, which exhibited better efficacy than MELD, MELD-Na and iMELD [27].…”
Section: Discussionmentioning
confidence: 99%